A first report of leptospirosis after liver transplantation. Issue 1 (30th January 2016) - Song, A.T.W.; Abas, L.; Andrade, L.C.; Andraus, W.; D'Albuquerque, L.A.C.; Abdala, E.
Abstract: Leptospirosis has been rarely reported in solid organ transplant recipients. We report the first case to our knowledge of leptospirosis in a liver transplant recipient who developed jaundice and renal insufficiency. We describe his favorable clinical progression and discuss the possible mechanisms involved in the more benign disease course. We also review the previously published cases of leptospirosis in solid organ transplant recipients. Although this disease does not appear to present any particularities in this context, we highlight the importance of clinical suspicion in this setting, particularly after liver transplantation.